2002
DOI: 10.1097/00024720-200206000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyaxial Pedicle Screws on Lumbar Construct Rigidity

Abstract: Pedicle screw constructs have been shown to increase fusion rates in the lumbar spine. Manufacturers have created pedicle screws with one or two degrees of freedom built into the screw head to allow for easier incorporation of the interlocking rod, but the effects of these screws on construct stiffness has not been tested. The purpose of this study is to compare and contrast the stiffness of lumbar pedicle screw constructs with and without the use of polyaxial pedicle screws. Nontapered, self-taping pedicle sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 11 publications
0
31
0
4
Order By: Relevance
“…When using monoaxial screws, the addition of an intermediate forces the surgeon to bend the connecting rod to accommodate the additional screw. Polyaxial screws, on the other hand, facilitate the installation of the connecting rod, and their biomechanical properties have been reported in several studies 141623. Stanford et al 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When using monoaxial screws, the addition of an intermediate forces the surgeon to bend the connecting rod to accommodate the additional screw. Polyaxial screws, on the other hand, facilitate the installation of the connecting rod, and their biomechanical properties have been reported in several studies 141623. Stanford et al 15.…”
Section: Discussionmentioning
confidence: 99%
“…pointed out that there were significant differences between the monoaxial screws and polyaxial screws in the bending stiffness, yield load, yield torque, and torsional stiffness in static tests ( P < 0.05). Shepard et al 16. suggested that polyaxial screws do not significantly decrease the stiffness of the construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By reducing the bending stresses, the polyaxial screw design may decrease the incidence of pedicle breakage. 28,37 However, compared with spinal constructs based on fixed-axis screws, constructs based on polyaxial screws have shown decreased rotational correction in vivo. 14 This liability has been suggested to be the result of the decreased rotational control of the spine due to the movement between the screw head and the screw's inherent polyaxial design.…”
Section: Discussionmentioning
confidence: 99%
“…Starting in the 1970s with simple systems that allowed a solid fixation between adjacent vertebrae [31], many modifications were made over the years [32]. In the 1990s polyaxial systems were developed [33,34], nowadays systems that allow a minimal invasive access surgery are the goal [35]. Those systems are useful especially for the therapy of osteoporotic vertebral body fractures, because in succession of minimal invasive approaches to the spine, less morbidity by the surgical intervention and earlier mobilization of the patients is possible.…”
Section: Additional Instrumentation Above and Below The Fracturementioning
confidence: 99%